High Potency of Volcanic Contribution to the ∼400 kyr Sedimentary Magnetic Record in the Northwest Pacific - Shin, Ji Young; Kim, Wonnyon; Hyeong, Kiseong (Frontiers in Earth Science, 2020)
As the northwest Pacific has been subject to varying terrigenous input linked to paleoclimate change, the concentration of magnetic minerals in deep-sea sediments is often utilized as a proxy to reconstruct the past atmospheric circulation in the Northern hemisphere. Volcanic materials account for a significant portion of the terrigenous input, but their contribution to sedimentary magnetic properties has not been carefully investigated. This study reveals the magnetic contribution and characteristics of volcanic materials, based on particle-size specific magnetic measurements on sediments that span the last 400 kyr for five size-fractions, including ranges typically attributed to fine eolian (< 2 and 2–8 μm) and coarse volcanic (8–31 and 31–63 μm) sediments. Such detrital origins were confirmed by SEM observations. Magnetic concentration (i.e., saturation isothermal remanent magnetization) of the coarse fractions is found to have a positive relationship with bulk values, making up a 23–68% portion. The volcanic contribution is more pronounced on the concentration of hard (> 100 mT) magnetic minerals, showing an increased portion of 32–74%. From coercivity spectra analysis, the coarse volcanic fractions are characterized by an abundance of the ~100 mT coercivity minerals, which can result in an increased average coercivity of bulk sediments. Around the study area, magnetic susceptibility records show synchronized variations with volcanic proportions in terrigenous sediments, validating their close relationship. Consequently, our results indicate that volcanic materials have a high potency of magnetic concentration, which can control bulk sedimentary signals in the northwest Pacific.